Resection Arthroplasty for Resistant Ulcers Underlying the Hallux in Insensate Diabetics. (August 2015) - Tamir, Eran; Tamir, Jeremy; Beer, Yiftah; Kosashvili, Yona; Finestone, Aharon S.
Background: Foot ulcers carry considerable morbidity in patients with peripheral neuropathy and frequently lead to foot amputation. The purpose of this study was to present our experience treating recalcitrant ulcers underlying the hallux interphalangeal joint in patients with diabetes mellitus (DM)–related neuropathy with a first metatarsophalangeal (MTPJ1) resection arthroplasty. Methods: We retrospectively reviewed the computerized medical files of patients with diabetic neuropathy treated with a MTPJ1 resection arthroplasty. We performed 28 arthroplasties on 20 patients with a mean age of 59 years. The patients had a diagnosis of DM for a mean of 10.7 years. Of the ulcers, 26 were grade 1A ulcers, and 2 were grade 2A ulcers (University of Texas score); the ulcer's mean age was 5.4 months. The mean dorsiflexion of the hallux before surgery was 46 degrees. Results: The primary ulcer recovered in a mean of 3.1 weeks. Major complications (wound dehiscence and infection) occurred in 6 of 28 operations. Patients returned to normal activity 4 weeks after all procedures except in the 6 patients with dehiscence. In a subgroup of patients with follow-up longer than a year, the ulcer recurred after 4 of 18 arthroplasties (22%) between 3 and 12 months due to postoperative hallux rigidus. In the remaining 14 of 18 arthroplasties (78%), there was no recurrence during a mean follow-up of 26 months. Conclusion: MTPJ1 resection arthroplasty may be considered in a patient with resistant plantar hallux ulcerations, even in the absence of hallux rigidus. As with all operations on neuropathic feet in patients with DM, the surgeon and the patient should be aware that there is a significant likelihood of complications, but most are treatable. Level of Evidence: Level IV, case series.